Therapies Targeting Epigenetic Alterations in Acute Kidney Injury-to-Chronic Kidney Disease Transition - Fumiaki Tanemoto; Imari Mimura (MDPI AG, 2022)
Acute kidney injury (AKI) was previously thought to be a merely transient event; however, recent epidemiological evidence supports the existence of a causal relationship between AKI episodes and subsequent progression to chronic kidney disease (CKD). Although the pathophysiology of this AKI-to-CKD transition is not fully understood, it is mediated by the interplay among multiple components of the kidney including tubular epithelial cells, endothelial cells, pericytes, inflammatory cells, and myofibroblasts. Epigenetic alterations including histone modification, DNA methylation, non-coding RNAs, and chromatin conformational changes, are also expected to be largely involved in the pathophysiology as a "memory" of the initial injury that can persist and predispose to chronic progression of fibrosis. Each epigenetic modification has a great potential as a therapeutic target of AKI-to-CKD transition; timely and target-specific epigenetic interventions to the various temporal stages of AKI-to-CKD transition will be the key to future therapeutic applications in clinical practice. This review elaborates on the latest knowledge of each mechanism and the currently available therapeutic agents that target epigenetic modification in the context of AKI-to-CKD transition. Further studies will elucidate more detailed mechanisms and novel therapeutic targets of AKI-to-CKD transition.